Studi Deskriptif: Filsafat Agama Dan Ruang Lingkup Kajian Pembahasannya - Iskandar Zulkarnaen (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
The terms philosophy and religion contain understandings that are understood counterintuitively by many. Philosophy in the way it works departs from reason, while religion departs from revelation. Therefore, this has a lot to do with thinking while religion has a lot to do with experience. Philosophy discusses something in order to see the measured truth, whether something is logical or not. Religion does not always measure truth logically because religion sometimes does not pay much attention to its logical aspects. In this study, researchers used qualitative-descriptive research with a type of library research. Where researchers read and analyzed the literature both books, journals and others carefully and can be accounted for academically this writing. In this study, researchers concluded that religious philosophy is a study of one's belief in religion based on logical thinking and conducted radically.